The Ministry of Industry, Trade and Small and Medium Projects Decree No. 287 of the Year 2015 On Imposing Final Precautionary Measures On Imports of Reinforcing Steel for Building Purposes Item = وزارة الصناعة والتجارة والمشروعات الصغيرة والمتوسطة قرار رقم 287 لسنة 2015 بفرض تدابير وقائية نهائية على الواردات من صنف حديد التسليح لأغراض البناء - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic